Photocatalytic Easy Recovery of Orthophosphates Contaminants in Water Using Amberlite‐732 Cationic‐Resin Exchanged by Ce3+and Ce3+‐Au3+ Species. Issue 13 (1st April 2022) - Rahmoune, PhDS. Nawel; Barama, Siham; Davidson, Anne; Montero, David; Selmane, Mohamed; Miche, Antoine; Benaliouche, Fouad; Barama, Akila
Abstract: This report discusses the efficiency of photo‐recovery of orthophosphate anions in water under visible irradiation using materials containing amorphous carbon, ceria and gold‐ceria species. Catalysts were obtained by the exchange of Amberlite‐732 polymeric‐resin with isolated Ce(III) and co‐mixing of Ce(III)‐Au(III) cations. Syntheses were developed for molar ratios Ce(III)/3H + =100 and Au(III)‐Ce(III)/3H + =0.01. Solids were treated at 800 °C under Air or Ar atmosphere then characterized by: X‐ray diffraction (XRD), Raman spectroscopy, scanning electron microscopy coupled to energy‐dispersive X‐ray spectroscopy (EDS), X‐ray photoemission spectroscopy (XPS) and UV‐visible spectroscopy. By XRD, non‐stoichiometric Ce2.658 S4 sulfide and particles of metallic gold are identified in Ce‐Au‐Amb‐Ar and in the case of Ce‐Au‐Amb‐Air, mixture of CeO2 and Au 0 is clearly observed. Moreover, XPS study of Ce3d emission spectra showed well resolved electronic states of the spin‐orbit Ce3d5/2 and Ce3d3/2 levels in the Ce 4+ and Ce 3+ oxidation states confirming coexistence of Ce(IV)/Ce(III). On the surfaces of both Ce‐Au‐Amb‐Air and Ce‐Au‐Amb‐Ar, XPS revealed metallic Au species. A certain amount of carbon, identified by EDS and XPS, corresponds to poorly ordered carbon formed by the resin decomposition during thermal treatments under Air and Ar. The UV‐vis spectroscopy was valuable to quantify the remaining PO4 3− anions in solution (at each moment of reaction) using "Molybdenum Blue" method. Photo‐recovery of orthophosphates under visible irradiation yields optimal trapping of ∼75 % of PO4 3− on Ce‐Au‐Amb‐Ar, attributed to a catalyst surface enrichment with Ce 3+ species, which promoted structural oxygen vacancies. Abstract : Ce‐Au‐Amb‐Ar is prepared by exchange of Amberlite‐732 resin with Ce 3+ ‐Au 3+ cation mixture and treated under Ar. This catalyst showed the best photo‐removal of PO4 3− anions in solution driven under visible irradiation. During reaction, non‐recovered PO4 3− are quantified using "Molybdenum‐Blue" method. The calculation of recovered PO4 3− indicated an optimal yield of 75 % obtained with Ce‐Au‐Amb‐Ar (clearest solution at 300 min of irradiation). Optimal photo‐removal is attributed to richer surface in Ce 3+ which responsible of production of ⋅O2 − and ⋅OH active species.